A Neutral Beryllium(I) Radical. Issue 38 (24th August 2021) - Czernetzki, Corinna; Arrowsmith, Merle; Fantuzzi, Felipe; Gärtner, Annalena; Tröster, Tobias; Krummenacher, Ivo; Schorr, Fabian; Braunschweig, Holger
Abstract: The reduction of a cyclic alkyl(amino)carbene (CAAC)‐stabilized organoberyllium chloride yields the first neutral beryllium radical, which was characterized by EPR, IR, and UV/Vis spectroscopy, X‐ray crystallography, and DFT calculations. Abstract : The reduction of a cyclic alkyl(amino)carbene (CAAC)‐stabilized organoberyllium chloride yields the first neutral beryllium radical, which was characterized by EPR, IR, UV/Vis spectroscopy and X‐ray crystallography. DFT calculations show significant spin density at beryllium and confirm donor–acceptor bonding between an alkylberyllium radical fragment and a neutral CAAC ligand.